What's to argue? A comparison of opposing viewpoints in context to the updated points of view reference center, with a nod to the original points of view reference center. Issue 3 (21st March 2016) - Nuttall, Harry D.
Abstract : Purpose: – The purpose of this paper is to provide an evaluative comparison of databases for argumentative/persuasive rhetoric. Design/methodology/approach: – This paper reviews and compares the databases in terms of the organization, types of information included and the ease of use. Findings: – To assist students in learning the rhetorical modes of argument and persuasion, some database vendors have developed proprietary electronic databases specific to this purpose. EBSCOhost's Points of View Reference Center and Gale/Cengage's Opposing Viewpoints in Context are two such databases. Which is better largely depends on the dominant user demographic of the educational institution. Both databases have strengths and weaknesses; therefore, the best results can be achieved by using them to complement one another. But if only one database can be selected, then that choice should most be influenced by the user demographic served. Research limitations/implications: – These databases have value as primers and introductions to research and writing in the rhetorical mode(s) of argumentation and persuasion, but students taking advanced classes should supplement them with more sophisticated searches in standard aggregator databases, which are not examined in detail in this paper. Originality/value: – This paper offers selectors an apples-to-apples comparison and analysis of two related resources, providing an insight about which can be used in the selection process.